Patient Satisfaction and Surgical Outcome After Oncoplastic Reconstruction following Radical Lumpectomy Versus Standard Lumpectomy: A Retrospective Cohort Study - Eyal Barkai; Yossi Namir; Orit Golan; Yoav Barnea; Ehud Arad; Tehillah S. Menes (European Journal of Breast Health, 2022)

(untitled)
Objective:Oncoplastic reconstruction (OR) enables widening of the indications for breast conserving therapy (BCT) and is redefining the limits of breast conservation. We examined the outcome and satisfaction of patients undergoing OR after radical lumpectomy (excision of more than 25% of the breast volume) and compared it to the outcome of women undergoing OR after standard lumpectomy.Materials and Methods:A retrospective, cohort study, including all patients undergoing OR after BCT between 2009 and 2018, was conducted. The ratio of volume of excision to breast volume was calculated using imaging studies. The study group included women that had more than 25% of their breast volume removed. The remainder formed the control group. Demographic characteristics, oncological treatment, and operation properties were collected. We compared post-operative complications, margin status and need for further surgery, as well as patient satisfaction, evaluated using the BREAST-Q Questionnaire.Results:One hundred and fifty women were included, of whom 24 (16%) comprised the study group with a mean breast volume reduction of 39%, while the remainder (mean volume reduction 8%) served as controls. Patient, tumor characteristics and treatment were comparable. There was a non-significant higher proportion of women in the radical group that underwent a second operation due to complications or positive margins [4/24 (16.7%) vs. 14/126 (11%), p = 0.4). Physical well-being was similar but satisfaction with breasts and with outcome was slightly lower for the study group. These differences did not reach statistical significance.Conclusion:Surgical outcome and patient satisfaction in women undergoing very extensive breast resections with OR are comparable to standard resections.